Membentuk Generasi Taat Ibadah Melalui Program Ubudiyah di Sb Ampang Selangor Kuala Lumpur Malaysia - Megawati Fajrin; Muqoffi; Moh. Khorofi; Wasik; Ali Wafa; Umar Faruq; Vina Eliana (Sekolah Tinggi Agama Islam Taruna Surabaya, 2025)
This research aims to determine the effectiveness of the ubudiyah program in shaping a generation of obedient worshippers at SB Ampang, Selangor, Kuala Lumpur. The background of this study is based on the reality that parents' busy work schedules lead to a lack of attention towards nurturing their children's worship practices. The ubudiyah program is introduced as an effort by the school to build the religious character of students through structured worship habituation. The research method used is a descriptive qualitative approach, with data collection techniques through observation, interviews, and documentation involving students, mentoring teachers, and parents. The research results indicate that the ubudiyah program runs effectively and has a significant impact on the worship quality of students, such as regularity in obligatory and Sunnah prayers, recitation of the Qur'an, as well as the formation of discipline and consistency in conducting worship. In addition to spiritual enhancement, this program also contributes to the intellectual development of students in understanding religious values. This success is supported by the role of guiding teachers, parental involvement, and a conducive school environment. However, challenges in program implementation were also found, such as the negative influence of gadgets and a busy academic schedule. The school responded to these challenges with intensive coaching strategies and adjustments to activity schedules. Overall, the ubudiyah program at SB Ampang has proven effective in shaping a generation that is devout in worship and possesses good character, and it can serve as a model for character education based on spirituality in the education environment Islam.